Peningkatan Kesehatan Mental Wirausahawan di Era Covid-19 dengan Penyuluhan Al-Qur’an - Dwi Sari Usop; Rospala Hanisah Yukti Sari; Candra Kurniawan; M Ziaurrahman; Norcahyono Norcahyono (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The 2019 coronavirus pandemic (Covid-19) had a broad influence on the economy in Indonesia. One of them was a little entrepreneur. Government regulation to maintain distance and decrease public places and characters from the swift spread of coronavirus caused many stores or businesses to close or greatly decrease the number of buyers or even no buyers. This condition certainly negatively affected little entrepreneurs, which could cause a decrease in immunity. One of the efforts to overcome was through giving Al Qur’an counseling and activity practice in daily life where was expected more increase the strength of the entrepreneur’s spirit and could face life in covid-19 and next.